Espectrofotometria de longo caminho óptico em espectrofotômetro de duplo-feixe convencional: uma alternativa simples para investigações de amostras com densidade óptica muito baixa Long optical path length spectrophotometry in conventional double-beam spectrophotometers: a simple alternative for investigating samples of very low optical density - André Luiz Galo; Márcio Francisco Colombo (Química Nova, 2009)
We describe the design and tests of a set-up mounted in a conventional double beam spectrophotometer, which allows the determination of optical density of samples confined in a long liquid core waveguide (LCW) capillary. Very long optical path length can be achieved with capillary cell, allowing measurements of samples with very low optical densities. The device uses a custom optical concentrator optically coupled to LCW (TEFLON® AF). Optical density measurements, carried out using a LCW of ~ 45 cm, were in accordance with the Beer-Lambert Law. Thus, it was possible to analyze quantitatively samples at concentrations 45 fold lower than that regularly used in spectrophotometric measurements.